Analysis Of Operational Performance On Raw Material Inventory And Machine Maintenance Cost (Case Studi at CV. Sari Wangi Cirebon City) - Intan Diahcinta Leonan; Rita Tri Yusnita; Suci Putri Lestari (Journal of Indonesian Management, 2022)
The purpose of this study was to determine and analyze the effect of raw material supplies and machine maintenance cost on the operational performance of CV. Sari Wangi. The research method used is a case study. The analysis tool uses multiple linear regression. The data used is a case study. The analysis tool uses multiple linear regression. The data used are primary data and secondary data. Based on the research results, it is known that the supply of raw material and machine maintenance simultaneously have a significant effect on the operational performance of CV. Sari Wangi. Raw material inventories partially have a have a significant effect on operational performance. Partial maintenance of machines does not have a significant effect on operational performance. Therefore, Cv. Sari Wangi management must pay attention to the supply of raw materials properly and pay attention to machine maintenance to improve the operational performance of CV. Sari Wangi.